Body image of the “their own vomiting figures” drawn by young children in 4 and 5 year old classes - Yokota, Saki; Baba, Noriko; Tsushima, Aiko; Takahashi, Toshiyuki; Mimura, Yukari (Japanese Journal of Health Education for Children, 2022)
This study examines health education in early childhood (the health field) from the perspective of the development of inner expression. This paper examines how young children perceive their inner bodies as an initial stage of research and clarifies s how this perception can be expressed through drawing and language. In parallel, we discuss the educational significance of expressing perception of the inner body. Accordingly, we analyzed children's drawings and remarks with the theme of “their own vomiting figures” by drawing body images using x-ray drawing method in 4 and 5 year old classes at comprehensive type of certified center for early childhood education and care. As a result, it was revealed that children in 4 and 5 year old classes could express by drawing and language based on their own body sensations, experiences, and imagination while applying the scientific knowledge they had acquired in the past. In addition, the expression of the body image of the infant has the characteristic of imagining and compensating for the lack of knowledge and experience, and at the same time, the development process of children in 4 and 5 year old classes is based on the scientific knowledge of the body image. It can be said that this is a transitional period in which it can be reflected in the expression. Consequently, it is considered that the childcare method of increasing the interest in one's body by imagining and enjoying the inside of the body is suitable for infants. Health education should not be started after acquiring a perfect body image, but the body image should be formed by providing health education and circularity providing health education will be important based on a formed body image. Also, in this process, it is necessary to have and express their own ideas, rather than trying to let them acquire correct knowledge efficiently.